Wearable microfluidics: fabric-based digital droplet flowmetry for perspiration analysis. Issue 5 (15th February 2017) - Yang, Yahui; Xing, Siyuan; Fang, Zecong; Li, Ruya; Koo, Helen; Pan, Tingrui
Abstract : Here we show for the first time a wearable microfluidic platform, named as digital droplet flowmetry (DDF), implemented on all-textile materials for real-time measurement of perspiration rates, via converting continuous flow into discrete droplets with identical volumes and assessing the flow rates by an electronic counting circuitry. Abstract : The latest development in wearable technologies has attracted much attention. In particular, collection and analysis of body fluids has been a focus. In this paper, we have reported a wearable microfluidic platform made using conventional fabric materials and laser micromachining to measure the flow rate on a patterned fabric surface, referred to as digital droplet flowmetry (DDF). The proposed wearable DDF is capable of collecting and measuring continuous perspiration with high precision (96% on average) in a real-time fashion over a defined area of skin. We have introduced a theoretical model for the proposed wearable interfacial microfluidic platform, under which various design parameters have been investigated and optimized for various conditions. The novel digitalized measurement principle of DDF provides fast responses, digital readouts, system flexibility, and continuous performance of the flow measurement. Moreover, the proposed DDF platform can be conveniently implemented on regular apparel or a wearable device, and has potential to be applied to dynamic removal, collection and monitoring of biofluids for various physiological and clinical processes.